Preferential Localization of Rat GAPDS on the Ribs of Fibrous Sheath of Sperm Flagellum and Its Expression during Flagellar Formation - Tanii, Ichiro (Japan Society of Histochemistry and Cytochemistry, 2007)
The proper assembly of sperm flagellar proteins is fundamental for sperm motility. The sperm- and spermatid-specific isoform of glyceraldehyde 3-phosphate dehydrogenase, GAPDS, is a flagellar protein indispensable for sperm flagellar movement. To obtain information on the assembly of the glycolytic enzyme into the flagellum, the precise localization of rat GAPDS in the flagellum and the stage of incorporation into the flagellum were examined using a monoclonal antibody. Immunolocalization of rat GAPDS was restricted to the fibrous sheath (FS) in the sperm flagellum, and was predominant in the circumferential ribs rather than the longitudinal columns. Immunoreactivity was first detected in the cytoplasm and flagella of the step-16 spermatids during the final step of FS formation. Together with the expression of other FS proteins, the present results indicate the sequential assembly of FS components, suggesting that the expression and transport of GAPDS is regulated in a coordinated manner during sperm flagellar formation.